Additional reflections on Putnam, Wright and Brains in Vats - Noonan, Harold W. (De Gruyter, 2016)
Putnam’s argument against the sceptical Brain-in-a-Vat hypothesis continues to intrigue. I argue in what follows that the argument refutes a particular kind of sceptic and make a proposal about its more general significance. To appreciate the soundness of the argument, I explain, we need to appreciate that the sceptic’s contention is that I cannot know that I am not a brain in a vat even if I am not. This is why in response to the sceptic it is legitimate to make a transition from knowing that a sentence is true to knowing the truth it expresses, which is the crucial move in the argument.